HABITS OF SUCCESS getting every student learning. - Fletcher-Wood, Harry ([S.l.] : ROUTLEDGE, 2021)
For students to benefit from lessons, they must attend, listen and try their best. But at times, almost all teachers struggle to manage classroom behaviour and to motivate students to learn. Drawing on decades of research on behavioural science, this book offers teachers practical strategies to get students learning. The key is students' habits. This book reveals simple yetpowerful ways to help students build habits of success. Harry Fletcher-Wood shows how teachers can use behavioural science techniques to increase motivation and improve behaviour. He offers clear guidance on topics such as using role models to motivate students, making detailed plans to help students act and building habits to ensure students keep going. The book addresses five challenges teachers face in encouraging desirable behaviour: Choosing what change to prioritise Convincing students to change Encouraging students to commit to a plan Making starting easy Ensuring students keep going Workshops, checklists and real-life examples illustrate how these ideas work in the classroom and make the book a resource to revisit and share. Distilling the evidence into clear principles, this innovative book is a valuable resource for new and experienced teachers alike.
Keywords: Motivation in education; Effective teaching; Classroom management; Academic achievement; EDUCATION / Secondary; EDUCATION / Educational Psychology; EDUCATION / Classroom Management